ENVISIONING HEALTHCARE SERVICE QUALITY, SAFETY AND EQUITY: FROM PUBLIC HEALTH CENTRE TO MILITARY HOSPITAL - Abdu Nafan Aisul Muhlis (Indonesian Journal of Health Administration, 2023)
The Indonesian Journal of Health Administration Volume 11 No.1 (2023) has been published. This edition covers a wide range of main topics, including enhancing healthcare management, expediting Covid-19 vaccination efforts, and improving public health programs within the community. Healthcare sustainability is expected to help accomplish the Sustainable Development Goals (SDG) by 2030. Gupta et al. discuss environmental sustainability in healthcare using elicitation techniques and found that the hospital in India tends to utilize natural resource optimally to minimize the usage of electricity and water, install a waste treatment plant, and be accredited by a quality assurance body to assure them prioritize the sustainability in healthcare services. Regarding healthcare service equity, Suar analyzed the implementation of social inclusion in military hospitals in Indonesia. This study revealed that patients from particular groups received exclusive care compared to other National Health Insurance or Jaminan Kesehatan Nasional (JKN) program members. However, it contrasts with the Indonesian government's commitment to offer its citizens equitable and inclusive healthcare.